The impact of economic structure and its effect on economic growth in Indonesia - Gita Aprianti; Ariusni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the impact of economic structure, particularly the agricultural sector, on Indonesia’s economic growth by incorporating investment, education, and health as supporting variables. Using panel data from 34 provinces over the period 2015–2024, the analysis is estimated with a Fixed Effect Model based on Chow and Hausman tests. Economic structure is proxied by the contribution of the agricultural sector to regional GDP. The results indicate that the agricultural sector has a positive and significant effect on economic growth, reflecting its role in employment creation, food security, and intersectoral linkages. Gross Fixed Capital Formation and education also show positive and significant effects, highlighting the importance of productive investment and human capital. In contrast, health exhibits a negative and significant effect, suggesting inefficiencies and unequal access to healthcare across regions. These findings imply that Indonesia’s economic growth is shaped by sectoral structure and the effectiveness of supporting factors, with policy relevance for strengthening agriculture, investment, education, and health system reforms.